A methodology for assess the on-load tap changers condition according to their health index - Cañar-Ramirez, Edgar Herney (2021)
This work presents a methodology to evaluate the OLTC on-load tap changer according to its health index, built from the operating principle and the general characteristics of this equipment. Given that interventions in this equipment have traditionally depended on maintenance and manufacturer records, this methodology seeks to migrate to maintenance based on the condition of the equipment, optimizing financial and personnel investments, generating greater reliability in the system and obtaining better asset management. To do this, initially the failure modes that may occur were identified, thus selecting the tests that most contribute to a diagnosis of OLTC, later the development of the methodology was carried out combining the tests in a weighted way and finally this methodology was integrated into the tool of estimation of the Transformer Health index developed by the High Voltage Research Group of the Universidad del Valle GRALTA. The methodology developed was validated with a case study.